Antioxidant, Enzyme Inhibitory and Calcium Oxalate Anti-crystallization Activities of Equisetum telmateia Ehrn. - TAŞKIN, TURGUT; DOĞAN, AHMET (My University, 2020)
Equisetum L. is the only genus of the Equisetaceae family, which commonly known as horsetails, in English and atkuyruğu or kırkkilit in Turkish. In traditional medicine, Equisetum telmateia Ehrh. is used in diseases of the urinary system, such as pyelonephritis, prostatic hypertrophy, and cystitis. Besides, this species is known to be used by humans to treat kidney stones or kidney sand. The extracts were obtained from the aerial parts of the E. telmateia using three different extraction methods (maceration, Soxhlet, ultrasonic bath) and their antioxidant (ABTS, CUPRAC), anti-urease and anticholinesterase activities were examined. Also, calcium oxalate anti-crystallization activity of Soxhlet methanol extract showing strong antioxidant activity was determined. Soxhlet methanol extract exhibited stronger ABTS radical scavenging (0.0676 mM Trolox/mg extract) and cupric ion reducing/antioxidant (4.351 mM Trolox/mg extract) activity than other extracts. Soxhlet methanol (65.528%) and maceration methanol (61.965%) extracts showed the strongest anticholinesterase activity. In the anti-urease assay, it was found that Soxhlet petroleum ether extract (15.302%) had the highest anti-urease activity. Furthermore, the data obtained showed that the Soxhlet methanol extract had high efficacy in the nucleation and aggregation phase of calcium oxalate crystals. These results prove that Soxhlet methanol extract has antioxidant, anticholinesterase and anti-crystallization capabilities. Therefore, this extract can be used in the future as an antioxidant and anticholinesterase agent as well as the treatment and / or prevention of stone formation.
Keywords: Tıp; Tarımsal Bilimler; Ziraat; Bitki Koruma; Fitopatoloji; Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyofizik; Biyokimya; Temel Bilimler; Medicine; Agricultural Sciences; Agriculture; Plant Protection; Phytopathology; Life Sciences; Biotechnology; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Fundamental Medical Sciences; Biophysics; Biochemistry; Natural Sciences; Tarım ve Çevre Bilimleri (AGE); Yaşam Bilimleri (LIFE); Bitki ve Hayvan Bilimleri; Biyoloji ve Biyokimya; Mikrobiyoloji; BİTKİ BİLİMLERİ; BİYOFİZİK; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Agriculture & Environment Sciences (AGE); Life Sciences (LIFE); PLANT & ANIMAL SCIENCE; BIOLOGY & BIOCHEMISTRY; MOLECULAR BIOLOGY & GENETICS; MICROBIOLOGY; PLANT SCIENCES; BIOPHYSICS; BIOCHEMISTRY & MOLECULAR BIOLOGY; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; Bitki Bilimi; Plant Science; Anti-crystallization; Anti-urease; Anticholinesterase; Equisetum telmateia